Sofrimento, conhecimento de si e corpo em Schopenhauer - TORRES, Joel Neres (Universidade Federal do Pará, 2014)
This research seeks to explain what constitutes the basis of suffering in Schopenhauer's philosophy, especially, in his magnum opus The World as Will and Representation. From a perspective of nature that mirrors the Will in its contradiction itself, go seek their degrees of objectification until reach the "summit" that presents itself in human consciousness, and through it, to understand that the knowledge produced as an appendix to serve as a help to the inherent complexity of this awareness, actually behaves like a "parasite" thus bringing through the path of individuality and body, a consciousness of anxiety and impotence. We seek to explore the reason of the limitation of this theoretical knowledge that faces the will and, in the other hand, explain how the sentimentality as a way of access to the will, in the body, it is presented as a possible solution to the perception of self, in which, if it works in conjunction with the theoretical knowledge, offers a "better consciousness" against the relentless suffering.